Misi Kultural-Ekologis sebagai Dialektika Kosmologi Aluk Mappurondo dan Agama Kristen di Mamasa, Sulawesi Barat - Saputra, Jefri Andri; Mordekai (Indonesian Journal of Theology, 2023)
This research explores the discord of belief between Aluk Mappurondo and Christianity in Mamasa, West Sulawesi, which is evident in residential segregation and the decline of relations between the two religions. As we aim to identify the common ground between them, the study uses a comparative approach to analyze the similarities and differences in the cosmologies of Aluk Mappurondo and Christianity. Despite their differing cosmologies, we find that Aluk Mappurondo and Christianity can coexist by defining and respecting each other's territories. They can also collaborate to uphold ethical values as well as demonstrate shared ecological concern in preserving forests and agricultural land in Mamasa.